2012
DOI: 10.1038/ncomms2168
|View full text |Cite
|
Sign up to set email alerts
|

Unique fingering instabilities and soliton-like wave propagation in thin acoustowetting films

Abstract: Acoustic-fluid interactions not only has had a long history but has recently experienced renewed scrutiny because of their vast potential for microscale fluid and particle manipulation. Here we unravel a fascinating and anomalous ensemble of dynamic 'acoustowetting' phenomena in which a thin film drawn from a sessile drop first spreads in opposition to the acoustic wave propagation direction. The advancing film front then exhibits fingering instabilities akin to classical viscous fingering, but arising through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 31 publications
5
86
1
Order By: Relevance
“…While the thicker pair of films and a single associated flow reversal was observed in an earlier study [7], none of the remaining phenomena has been reported. The ability to form a submicrometre film, and-between the thinner pair of these three film thickness ranges-a second flow reversal and an associated unstable thickness region have now been discovered and found to lead to the formation of sharply defined film protrusions and depressions that bizarrely move in different directions depending on their particular thicknesses.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…While the thicker pair of films and a single associated flow reversal was observed in an earlier study [7], none of the remaining phenomena has been reported. The ability to form a submicrometre film, and-between the thinner pair of these three film thickness ranges-a second flow reversal and an associated unstable thickness region have now been discovered and found to lead to the formation of sharply defined film protrusions and depressions that bizarrely move in different directions depending on their particular thicknesses.…”
Section: Introductionmentioning
confidence: 88%
“…While such Eckart flows usually dominate large sessile drop translation experiments, in which the drops are observed to move along the SAW propagation direction [15,16], we have shown that these flows are also dominant in the film in figure 2d(iii) and previously in the solitary wave-like ridges in [7], as long as the thickness of these features exceed the sound wavelength (h λ ). …”
Section: Critical Transition Thickness H C 2 Between Thick and Intermmentioning
confidence: 95%
See 3 more Smart Citations